2017
DOI: 10.1371/journal.pone.0181768
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of pre-surgical infant orthopedics in patients with non-syndromic cleft lip and/or palate: A systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundNon-syndromic clefts lip and/or palate (CL/P) defects may have manifold significant and detrimental consequences for the affected individuals and their family environment. Although the use of pre-surgical infant orthopedics (PSIO) was introduced as a means to improve management and treatment outcomes, there still remains a controversy.ObjectiveTo investigate the effectiveness of PSIO in patients with non-syndromic CL/P and evaluate the quality of the available evidence.Search methodsSearch without re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 89 publications
0
31
0
4
Order By: Relevance
“…16 Different studies (including meta-analysis) have described the absence of scientific evidence supporting the use of NAM for cleft lip nose repair. 11 , 17 19 Significant relapse of the deformity has been observed after using nasal moldings, 20 and good outcomes were observed only in combination with primary rhinoplasty. 21 23 The Taiwanese group from Chang Gung University demonstrated that nasal molding has a short-term effect, and only surgery may guarantee a long-term effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Different studies (including meta-analysis) have described the absence of scientific evidence supporting the use of NAM for cleft lip nose repair. 11 , 17 19 Significant relapse of the deformity has been observed after using nasal moldings, 20 and good outcomes were observed only in combination with primary rhinoplasty. 21 23 The Taiwanese group from Chang Gung University demonstrated that nasal molding has a short-term effect, and only surgery may guarantee a long-term effect.…”
Section: Discussionmentioning
confidence: 99%
“…The last meta-analysis published by Hosseini in 2017 concluded that there is limited evidence to support the short- or long-term effectiveness of presurgical NAM in cleft lip and palate patients. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Different reviews and meta-analysis have been published during the last years addressing the effects of NAM in cleft lip and palate surgery. 33 , 34 A 2017 meta-analysis by Hosseini et al 34 suggested further research to reach more relevant recommendations. Two recent reviews by Maillard et al 35 in 2017 and Liu et al 36 in 2018 concluded that the use of NAM offers positive aesthetical effects.…”
Section: Discussionmentioning
confidence: 99%
“…There remains ongoing debate as to the efficacy of presurgical intervention in the management of CLP. Aspects such as cost–benefit of treatment and the influence of PSO treatment on facial growth and arch form in the longer term remain controversial with the current evidence being of low quality to make any conclusive recommendations (Uzel and Alparslan, 2011; Hosseini et al, 2017). Although further high-quality studies are required, there is an emerging body of evidence that have highlighted promising results from the use of techniques such as nasoalveolar molding (Spengler et al, 2006; Abbott and Meara, 2012).…”
Section: Discussionmentioning
confidence: 99%